Autochthonous chikungunya and dengue fever outbreak in Mainland France, 2010-2018. (13th November 2019) - Franke, F; Giron, S; Cochet, A; Jeannin, C; Leparc-Goffart, I; de Valk, H; Jourdain, F; de Lamballerie, X; L'Ambert, G; Paty, M C
Abstract: Background: Aedes albopictus, vector of dengue and chikungunya viruses, is implanted in mainland France, exposing to the risk of autochthonous transmission. Since 2006, epidemiological and entomological surveillance activities aim to prevent or limit the occurrence of autochthonous cases. We aimed to describe episodes of transmission and control measures implemented in order to reflect on surveillance activities. Methods: We reviewed all publications and documents produced on autochthonous transmission episodes in France and surveillance protocols. We reviewed surveillance activities, investigation methods and control measures implemented. Results: Between 2010 and 2018, eight episodes of autochthonous dengue fever transmission and three of chikungunya were recorded in mainland France. All of them occurred in the South east of France, between July and October, when vector density was the highest. Transmission areas were limited to single domestic houses located in discontinuous urban areas. Only two episodes happened in two distinct areas. Chikungunya episodes led to 31 cases and dengue fever episodes to 23 cases. Most cases were identified by door-to-door investigations set-up in transmission areas. We isolated serotypes 1 and 2 for dengue and East Central South Africa lineage for chikungunya in autochthonous cases. Adulticide vector control measures were effective in controlling transmission. Seven episodes of transmission were due to failure in identifying primary imported cases. Four episodes occurred because of the absence or the lack of vector controls measures around primary imported cases. Conclusions: Surveillance activities, and autochthonous cases investigations, were effective in limiting the extent of transmission, but were highly demanding for surveillance actors. Identified causes of transmission highlight the need of regular awareness campaigns targeting physicians and biologists. Key messages: Effectiveness of the surveillance system of dengue, chikungunya and zika viruses, and autochthonous cases investigations. Needs of awareness and training courses targeting health professionals to the risk represented by these viruses.